Automotive computer systems - Knowles, Don; Erjavec, Jack (Today's technician., 1996)
This state-of-the-art resource provides comprehensive coverage of all types of computer systems and includes the ASE Task Lists for Advanced Engine Performance and OBD-II. Every automotive area, from engine control to transmissions, brakes and suspension and steering, can be found in Automotive Computer Systems. Two book set includes a shop manual and a classroom manual, - See more at: http://www.betterworldbooks.com/today-s-technician-id-0827368844.aspx&utm_source=Affiliate&utm_campaign=Text&utm_medium=booklink&utm_term=3630151&utm_content=Homepage#sthash.jzKB9j94.dpuf